2014
DOI: 10.1001/jama.2014.4573
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of the Older Patient

Abstract: Geriatric conditions may be associated with adverse surgical outcomes. A comprehensive evaluation of treatment goals and communication of realistic risk estimates are essential to guide individualized decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
182
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(196 citation statements)
references
References 91 publications
5
182
0
3
Order By: Relevance
“…In one of the randomised controlled trials included in the review, CGA reduced the rate of complications by 11.8% and the time to 'fit for discharge' by 0.5 days in patients undergoing elective orthopaedic surgery (Huddleston et al, 2004). In addition, the use of preoperative geriatric assessment markers to assess patient frailty has demonstrated good predictive ability for postoperative complications, discharge to a nursing facility, and 6-month mortality in patients undergoing major surgery (Robinson et al, 2009;Makary et al, 2010;Oresanya et al, 2014). Determining which patients are at risk for adverse postoperative events using CGA can also help guide preoperative and postoperative management of surgical patients in several other ways.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the randomised controlled trials included in the review, CGA reduced the rate of complications by 11.8% and the time to 'fit for discharge' by 0.5 days in patients undergoing elective orthopaedic surgery (Huddleston et al, 2004). In addition, the use of preoperative geriatric assessment markers to assess patient frailty has demonstrated good predictive ability for postoperative complications, discharge to a nursing facility, and 6-month mortality in patients undergoing major surgery (Robinson et al, 2009;Makary et al, 2010;Oresanya et al, 2014). Determining which patients are at risk for adverse postoperative events using CGA can also help guide preoperative and postoperative management of surgical patients in several other ways.…”
Section: Discussionmentioning
confidence: 99%
“…Validated risk-stratification tools provide objective data to surgeons to one aspect of a patient's operative risk (cardiovascular, pulmonary, psychological, etc. ), 8,10,16,23,26,29,30 but their utility to spinal surgery is limited. Given that the vast majority of spinal procedures are elective, surgical candidates are generally without any active exacerbations of their medical problems.…”
mentioning
confidence: 99%
“…Specifically, 3% to 5% of elderly people who have had hip and knee surgeries would experience acute confusion or delirium for a specific period. Therefore, insufficient pre-surgery assessments and post-surgery complications are factors related to elderly delirium [6,19]. The functional, cognitive, psychosocial, and other factors are decreases in energy, activities of daily living and instrumental activities of daily living, and cognition, as well as increases in sleep disturbances, depression, social isolation, long-term bed rests, environmental overstimulus, catheter use, and need for restraint [2,5,[7][8][9][10]14,16,17].…”
Section: Related Factors Of Elderly Deliriummentioning
confidence: 99%
“…Moreover, delaying the time of delirium might increase the incidence of illness, patients' dependence, the needs of nursing homes, and death rates because of the heavy burden on the health care system and society [1,4,5,7,9,10,14,16,18,19]. In addition, a study reported that urinary tract infection (UTI) rates in elderly patients with delirium ranged from 25.9% to 32% compared with 13% in those without delirium; in patients with UTI, delirium rates ranged from 30% to 35%, compared with 7.7% to 8% in those without UTI [11].…”
Section: Consequences Of Elderly Deliriummentioning
confidence: 99%